Harnessing Africa's untapped solar energy potential for health (The World Health Organization, 2014)
For a continent with abundant sunlight and poor electricity grid coverage, Africa makes very little use of solar power in the health sector. Given recent initiatives, this may be set to change. Gary Humphreys reports.